The yeast his3 promoter contains at least two distinct elements. - Struhl, K (1982)
Phenotypic analysis of 65 mutations indicates that the yeast his3 promoter is composed of at least two separate regions of DNA. Each is necessary, but neither is sufficient for wild-type levels of his3 expression. Deletion mutations that destroy either promoter element express his3 poorly or not at all. The upstream element is located between 112 and 155 base pairs before the site of transcriptional initiation (nucleotides -112 to -155). A comparison of derivatives strongly suggests that the downstream element maps somewhere between nucleotides -32 and -52 and includes a sequence between nucleotides -45 and -52. This location coincides with sequences conserved before most eukaryotic genes(the TATA box region). By using derivatives in which his3 sequences are replaced by a small fragment of coliphage M13 DNA, three properties of the his3 promoter were established. First, his3 TATA box deletions fail to express his3 because they lack specific sequences and not because they disrupt spacing relationships between other sequences. Second, the TATA box region can be replaced functionally by the one orientation of the M13 DNA fragment that contains a TATA-like sequence. Third, the distance between the two elements (normally 90 base pairs) can be varied between 40 and 160 base pairs without markedly affecting promoter function. These results strongly suggest that yeast RNA polymerase II, unlike its Escherichia coli counterpart, does not bind simultaneously to both promoter elements, and they add further support to the view that the upstream element is not part of a transcriptionally competent binding site. This ability of the his3 upstream promotor element to act at a long and variable distance is similar to properties of viral enhancer sequences and is reminiscent of position effects in yeast.